2019
DOI: 10.17305/bjbms.2019.4002
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum chemerin and inflammatory factors with type 2 diabetes macroangiopathy and waist-to-stature ratio

Abstract: Chemerin is an adipocytokine that participates in glycolipid metabolism; however, its association with type 2 diabetes (T2DM) with lower extremity macroangiopathy (T2DM-V) has rarely been reported. This study explored the association of chemerin and inflammatory factors with body fat parameters, glucolipid metabolism, and insulin resistance (IR) in T2DM and T2DM-V. Patients were classified into normal glucose regulation (NGR), T2DM, and T2DM-V groups. Serum chemerin, glucolipid metabolic parameters, transformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…MiRNAs promotes mRNA degradation or inhibits translation process to affect the progression of NSCLC by complementary pairing with the 3’UTR of the target mRNA. For example, miR-608 impedes proliferation and metastasis of NSCLC cells via targeting the BRD4 [ 31 ]. MiR-7-5p functions as a tumor suppressor o block the progression of NSCLC via targeting PAK2 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs promotes mRNA degradation or inhibits translation process to affect the progression of NSCLC by complementary pairing with the 3’UTR of the target mRNA. For example, miR-608 impedes proliferation and metastasis of NSCLC cells via targeting the BRD4 [ 31 ]. MiR-7-5p functions as a tumor suppressor o block the progression of NSCLC via targeting PAK2 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are corroborated by earlier and recent findings [ 62 , 67 ]. In the current study, higher levels of chemerin were observed in the T2DM patients and were closely associated increasing WHR and BMI, which is in agreement with the work of Yang et al, who reported a positive correlation between chemerin levels and BMI and other anthropometric indices [ 68 ]. Our results are also in agreement with a previous study conducted on a section of Saudi women by Habib et al, who reported higher levels of chemerin in T2DM patients, and a good correlation with insulin resistance and adiposity [ 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…A number of studies have shown an association between increased circulating chemerin levels with obesity and T2DM in humans, correlating with markers of insulin resistance and inflammation [ 101 , 102 , 103 , 104 ], while exercise, diet intervention, and bariatric surgery decrease its levels [ 105 , 106 , 107 , 108 ]. Moreover, both chemerin and CMKLR1 are upregulated in adipose tissue from obese patients, where the pro-inflammatory cytokine TNFα increases chemerin mRNA expression in visceral adipocytes [ 109 ], which suggests that the low-grade inflammation observed in obesity could contribute to chemerin expression in the adipose tissue [ 110 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%